Naval sonar disrupts foraging in humpback whales: - Sivle, L.D.; Wensveen, P.J.; Kvadsheim, P.H.; Lam, F.P.A.; Visser, F.; Curé, C.; Harris, C.M.; Tyack, P.L.; Miller, P.J.O. (Inter-Research, 2016)
Modern long-range naval sonars are a potential disturbance for marine mammals and can cause disruption of feeding in cetaceans. We examined the lunge-feeding behaviour of humpback whales Megaptera novaeangliae before, during and after controlled exposure experiments with naval sonar by use of acoustic and motion sensor archival tags attached to each animal. Lunge-feeding by humpback whales entails a strong acceleration to increase speed before engulfing a large volume of prey-laden water, which can be identified by an acoustic signature characterized by a few seconds of high-level flow-noise followed by a rapid reduction, coinciding with a peak in animal acceleration. Over 2 successive seasons, 13 humpback whales were tagged. All were subject to a no-sonar control exposure, and 12 whales were exposed to 2 consecutive sonar exposure sessions, with 1 h between sessions. The first sonar session resulted in an average 68% reduction in lunge rate during exposure compared to pre-exposure, and this reduction was significantly greater than any changes observed during the no-sonar control. During the second sonar session, reduction in lunge rate was 66% during sonar exposure compared to the pre-exposure level, but was not significant compared to the no-sonar control, likely due to a larger inter-individual variability because some individuals appeared to have habituated whereas others had not. Our results indicate that naval sonars operating near humpback whale feeding grounds may lead to reduced foraging and negative impacts on energy balance. © 2016 The authors.